Aging, Disability, and Informal Caregivers: A Cross-sectional Study in Portugal - Pego, Maria Ana; Nunes, Carla (Frontiers in Medicine, 2018)
Objectives: Ageing is ‘pushing’ states to rethink long-term care policies in several dimensions. This study aims to characterise the reality of the dependent older person regarding demographic and health characteristics; describe the informal carers; and understand the availability of informal care. Methods: A cross-sectional study was developed in Portugal in 2013. Descriptive statistical analyses and binary logistic analysis were conducted. Results: Results show that informal long-term care sector is primarily aimed at older people with severe limitations in their activities of daily living and the chronically ill, particularly older women. Additionally, 39.5% of dependent older persons doesn't have informal care and only in cases of extreme need does informal aid arise. Discussion: Results show a very critical situation for both social groups (older persons and caregivers) and an alarming situation in the near future (ageing and reduced availability of informal caregivers) unless a new approach for long-term care arises.